COAL CONSUMPTION AND ECONOMIC GROWTH IN NIGERIA: A TWO-STEP RESIDUAL-BASED TEST APPROACH TO COINTEGRATION - Nasiru, Inuwa (European Scientific Journal, ESJ, 2012)
This examines the relationship between coal consumption and economic growth for Nigeria over the period 1980-2010 by using a two-step residual-based approach to co integration and Granger causality test. The empirical results of this study reveal that coal consumption and economic growth in Nigeria are moving together in the long run. Also, the causality results indicate a unidirectional relationship running from economic growth to coal consumption. This means that continuous economic growth simultaneously generates a continuous rise in coal consumption. In this case, coal consumption is fundamentally driven by real GDP. Since economic growth directly causes coal consumption and not vice versa, the closure or slow down of coal consumption in Nigeria should not have, in general, a significant negative impact on Nigerian economy.